Cost-effective and performance analysis of thermoelectricity as a building cooling system; experimental case study based on a single TEC-12706 commercial module. (October 2021) - Tian, Man-Wen; Aldawi, Fayez; Anqi, Ali E.; Moria, Hazim; Dizaji, Hamed Sadighi; Wae-hayee, Makatar
Abstract: Application of thermoelectricity as the building air cooling system has not been commercialized yet. However, remarkable eco-friend characteristics of thermoelectricity encourages the researchers to enthusiastically work on different aspects of Peltier cooler to make its performance competitive with other cooling techniques. The contribution of this research is to explicitly clarify the real cooling cost made by a single popular and affordable thermoelectric module in the market under different working conditions and identify how the effective parameters can impact the cooling cost and performance of the cooler. To reach the aim of this research, a laboratory-scale thermoelectric air-water based cooler is fabricated to obtain the behavior of thermoelectric cooler under different air flow rates, room (air intake) temperatures, input power and so on. In the next step, the obtained results are employed to analyze the cost-effective features of the cooler under the mentioned working conditions. Based on the results, cost per kWh of cooling by a thermoelectric module can vary between 0.7 and 1.4 dollar depending on the range of mentioned parameters. It is interesting that, an extremum point is observed for input power of 23 W through which the cost of air cooling process is minimized and then is increased. Hence, number of employed thermoelectric modules in real big size cooler will be a key parameter to allocate an optimum input power for any individual thermoelectric module. Moreover, the cost of cooling is reduced for warmer air temperatures which shows the suitability of thermoelectric coolers for hot regions.